Effect of single-dose methotrexate injection to prevent neoplastic changes in high risk complete hydatidiform mole: A randomised control trial - Jhuma Biswas; Shyamal Dasgupta; Mallika Datta; Mousumi Datta; Santa Saha; Parthapratim Pradhan (Journal of Family Medicine and Primary Care, 2022)
Background: Complete hydatidiform mole affects women in their reproductive age. About 15-20% develops persistent molar gestational trophoblastic neoplasia (GTN), which is linked with delayed (beyond 56 days) normalization of serum βHCG after surgical evacuation. Objective: The objective of the article is to shorten the duration of normalization time of βHCG with single-dose methotrexate injection in women with high risk complete hydatidiform mole (CHM) after suction evacuation. Methods: Total 76 women with CHM were randomized into intervention and control groups. In the intervention arm (n = 34) women received single dose 100 mg intramuscular methotrexate injection post evacuation and the control group (n = 42) had standard care. Surveillance was done in both groups at two weeks intervals for next six months and duration of normalization of βHCG level was recorded. Results: Total 94.7% women completed follow-up. Mean of normalization time was significantly lower in the intervention group compared to controls (9.7 weeks versus 14.7 week; P < 0.01). Time to event curve showed significantly earlier cumulative normalization time for the intervention group. Conclusion: Single-dose 100 mg methotrexate injection is a low-cost, simple intervention to help one out of three women with CHM with high-risk features to achieve normalization of βHCG within 56 days. This might be helpful for people in resource-poor countries where adherence to prolonged surveillance is poor.